THE INITIAL ECHINODERMS COMMUNITY STRUCTURE IN SEAGRASS BED OF MARINE TOURISM AREA: MAHITAM ISLAND AND KETAPANG BEACH, LAMPUNG - Muhaemin, Moh; Priambodo, Mohammad Fadhil; Susanti, Oktora; Efendi, Eko (AQUASAINS, 2023)
Lampung is one of national marine tourism destination. Seagrass is one of fragile coastal ecosystem and it is a habitat and feeding ground for a number of Echinoderms species.  Echinodermata are nutrient recyclers that will in turn provide benefits to the seagrass ecosystem. This research aimed to assess the community structure of Echinoderms and seagrass as well as the relationship between Echinoderms abundance, seagrass densities, and water quality in Mahitam Island and Ketapang Beach. Observations were conducted at 7 stations, namely 3 stations on Ketapang Beach and 4 stations on Mahitam Island. Observations included the type and number of echinoderms, as well as the type, number of individuals, and number of seagrasses stands. Habitat quality that was observed were included water quality such as temperature, salinity, pH, DO (dissolved oxygen), current speed, brightness, and TOM (total organic matter) and also observed substrate type at each station. The result elucidated nine species of echinoderms and 4 species of seagrasses were found in both study sites. The average value of Echinoderms diversity index in Mahitam Island and Ketapang Beach was low. The uniformity index of Echinoderms in Mahitam Island was medium and Ketapang Beach was low. The dominance index of Echinoderms on Mahitam Island was categorized as low and Ketapang Beach was considered high. There was a domination of an Echinoderms species in some stations. The association between Echinoderms abundance, seagrass density and habitat quality in both locations showed a positive relationship and was influenced by the habitat quality parameters of seagrasses.